2021
DOI: 10.1126/scitranslmed.abf3637
|View full text |Cite
|
Sign up to set email alerts
|

Toward predicting CYP2D6-mediated variable drug response from CYP2D6 gene sequencing data

Abstract: Pharmacogenomics is a key component of personalized medicine that promises safer and more effective drug treatment by individualizing drug choice and dose based on genetic profiles. In clinical practice, genetic biomarkers are used to categorize patients into *-alleles to predict CYP450 enzyme activity and adjust drug dosages accordingly. However, this approach leaves a large part of variability in drug response unexplained. Here, we present a proof-of-concept approach that uses continuous-scale (instead of ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…CYP2D6, another gene with allelic variants and encoding enzymes with variable degrees of activity, is associated with the development of hepatotoxicity after use of certain pharmaceutical agents. The CYP2D6 gene is polymorphic with over 150 allelic variants (https://www.pharmvar.org/gene/CYP2D6) [20][21][22][23]. The existing variation in the frequencies of alleles of polymorphic pharmacogenes among different ethnic groups may be responsible for severe adverse reactions to, or altered efficacy of, a wide variety of drugs.…”
Section: Figure 1 the Total Number And Length Of Roh Identied Across ...mentioning
confidence: 99%
“…CYP2D6, another gene with allelic variants and encoding enzymes with variable degrees of activity, is associated with the development of hepatotoxicity after use of certain pharmaceutical agents. The CYP2D6 gene is polymorphic with over 150 allelic variants (https://www.pharmvar.org/gene/CYP2D6) [20][21][22][23]. The existing variation in the frequencies of alleles of polymorphic pharmacogenes among different ethnic groups may be responsible for severe adverse reactions to, or altered efficacy of, a wide variety of drugs.…”
Section: Figure 1 the Total Number And Length Of Roh Identied Across ...mentioning
confidence: 99%
“…However, the current classification of CYP2D6 enzyme activities based on the star-allele gene definitions has proven to be a suboptimal predictor for enzyme activity (44). More recent research by Van der Lee et al (45) supported this by confirming that building a predictive model based on the complete CYP2D6 gene sequence gives better predictive values for the gene function than a model built solely based on the star-alleles. By generating complete consensus sequence, CoLoRGen can phase additional mutations, thereby allowing a more accurate gene function predictions.…”
Section: Comprehensive Genotyping Of the Na12878 Cyp2d6-cyp2d7 Locus ...mentioning
confidence: 99%
“…This information can also be used to optimize models to predict drug response by taking phasing and full gene sequencing into account. Indeed, recently a continuous scale model based on full gene variants data explored by long-read sequencing and neural network improved the explanation of CYP2D6 activity variability from 54% to 79% compared with the conventional phenotype classification ( van der Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the conventional variant to metabolizer phenotype interpretation which only includes a limited number of well-known variants with fixed effects inevitably leads to missing information. Previous studies have shown that, at least for CYP2D6, a continuous model is able to better explain the enzyme activity ( McInnes et al, 2020 ; van der Lee et al, 2021 ). It can be expected that the same principle holds true for CYP3A as well.…”
Section: Introductionmentioning
confidence: 99%